Dampak Implementasi Kebijakan Pendidikan Seks Di Smp Negeri 2 Meureubo Terhadap Perilaku Peserta Didik - Amalia , Roza; Pratama, Agus (Jurnal Administrasi Politik dan Sosial, 2025)
Cases of sexual violence such as free sex and promiscuity in Indonesia continue to occur. SMP Negeri 2 Meureubo is the school institution that has this case. Sexual education is sex education which is very important to be implemented in first level educational institutions. This research aims to see the impact of implementing sexual education policies at SMP Negeri 2 Meureubo on students. Using descriptive qualitative methods with policy theory by George C. Edward III, namely by looking at four indicators, including: Communication, Resource, Disposition, Bureaucratic Structure. The research results show that the impact of the program is seen in increasing students' awareness of the importance of maintaining behavior and protecting themselves from sexual harassment. However, challenges remain in changing the behavior of some students completely. With continued efforts, such as additional training and guidance in the future, this program has the potential to continue to strengthen the formation of positive attitudes and behavior in students.